La Libreria privata del Marchese Suddecano Gabriello Riccardi Il fondo manoscritti - Bartoletti, Guglielmo (Fonti storiche e letterarie - Edizioni cartacee e digitali, 2017)
This volume reconstructs the events of the private library of the Marquis Subdean Gabriello Riccardi (1705-1798), which at the end of its development will be joined and merged with that of the Family, today known as the Riccardiana Library. The research focuses in particular on the Manuscripts Fund, which was definitely the most relevant and precious part. The final result of the present study has produced both a topographical catalogue, which reconstructs the physical layout that these manuscripts had in their original location, and an alphabetical catalogue, according to the 18th Century original. Finally, the historical essay highlights the events that led this famous library, now unified by Gabriello's will, to save itself from dispersion and remain intact as we know it today. The publication is enriched by a Repertorial Section, available with open access in the digital version of the volume (eBook), which presents a series of documents, catalogues and indexes obtained from the study on the Library of Gabriello Riccardi.